Corrigendum: Quality of life and quality of education among physiotherapy students in Europe - Schramlová, Michaela; Řasová, Kamila; Jonsdottir, Johanna; Pavlíková, Markéta; Rambousková, Jolana; Äijö, Marja; Šlachtová, Martina; Kobesová, Alena; Žiaková, Elena; Kahraman, Turhan; Pavlů, Dagmar; Bermejo-Gil, Beatriz María; et al. (Frontiers in medicine, 2024)
[This corrects the article DOI: 10.3389/fmed.2024.1344028.].
Keywords: students; sleep; physical activity; physiotherapy; nutrition; stress